Inflammatory and immune mechanisms in COPD - Barnes, Peter (Henry Stewart Talks, 2012)
Amplification of inflammation in COPD, Inflammatory cells involved in COPD, Role of macrophages in orchestrating inflammation, Defective macrophage phagocytosis in COPD, Mechanism of corticosteroid resistance in COPD, Role of Nrf2